Preparation method of high-alumina fly ash-kaolin composite ceramic membrane
By using high-volume fly ash and kaolin as raw materials, and by extending the sintering and insulating time and using spraying method to prepare the filter layer, the problems of high production cost of ceramic membranes, small water flux and large filter layer pore size are solved, and ceramic membranes with low cost, high water flux and high filtration accuracy are achieved.
Patent Information
- Application Number
- CN202510125454.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-27
AI Technical Summary
The existing ceramic membrane has high production costs, small water flux and large filter layer pore size, making it difficult to meet the needs of industrial water treatment.
High-aluminum fly ash and kaolin are used as raw materials to prepare a filter layer by extending the sintering and insulating time and using spraying method to improve the porosity and water flux of the ceramic membrane while reducing costs.
High-aluminum fly ash-kaolin composite ceramic membrane with low cost, high water flux and high filtration accuracy is achieved, which significantly improves the performance and economicality of the ceramic membrane.
Smart Images

Figure CN119793239A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic membranes, in particular to a method for preparing a high-alumina fly ash-kaolin composite ceramic membrane. Background Art
[0002] With increasingly stringent sewage discharge standards, membrane separation technology has received more and more attention in the field of water treatment compared to traditional separation methods. At present, membrane separation is mainly divided into inorganic membrane and organic membrane according to materials. Organic membrane is affected by COD, pH and other conditions, and has certain limitations in the field of industrial water treatment with complex water quality. Inorganic membrane ceramic membrane not only has high chemical stability, but also has the advantages of high temperature resistance, corrosion resistance, and high mechanical strength. It has been widely used in recent years. At present, common raw materials for ceramic membrane production include Al2O3, ZrO2, TiO2, etc. Their expensive prices and high sintering temperatures make the cost of ceramic membranes high. Fly ash, as a solid waste generated by coal combustion, contains a large amount of aluminum oxide and silicon oxide. At high temperatures, it can form mullite with good mechanical strength and is a cheap material for preparing ceramic membranes. Applying it in the field of ceramic membranes can not only reduce the preparation cost of ceramic membranes, but also turn fly ash into treasure.
[0003] Chinese patent CN116375453B discloses a method for preparing a high-alumina fly ash ceramic support. The low-cost support has catalytic self-cleaning properties, but the water flux is not high (only 1800-4100 L / h·m 2 ·MPa), if the composite filter layer will further reduce the water flux. Chinese patent CN109173748A discloses a method for preparing a fly ash ceramic membrane, using fly ash of different particle sizes as raw materials to prepare an asymmetric ceramic membrane with a support, a transition layer and a separation layer. Multiple coatings make the preparation process extremely cumbersome, and the prepared separation membrane has a large pore size (1-2.2μm) and low filtration accuracy. Chinese patent CN109126482B discloses a method for preparing a fly ash-alumina double-layer composite microfiltration ceramic membrane, which uses an impregnation method to coat a layer of alumina microfiltration membrane on a fly ash carrier to obtain a composite ceramic membrane with a pore size of 0.1-0.3μm, thereby improving the separation accuracy. However, the addition of alumina significantly increases the cost. In view of the above problems of high production cost, small water flux, large pore size of the filter layer, a high-aluminum fly ash-kaolin composite ceramic membrane with low cost, large water flux and small pore size of the filter layer is invented. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a high-aluminum fly ash-kaolin composite ceramic membrane in view of the shortcomings of the current technology. The method uses high-aluminum fly ash as a raw material to prepare a support body, and by extending the heat preservation time, the support body increases the porosity and water flux while the compressive strength can still meet the technical requirements; at the same time, low-priced kaolin is used as a raw material to prepare the filter layer, and the one-time coating reduces the cumbersome process of coating. The present invention improves the filtration accuracy of the ceramic membrane while reducing the cost.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a high-alumina fly ash-kaolin composite ceramic membrane, the method comprising the following steps:
[0007] (1) Preparation of support
[0008] The high-alumina fly ash, pore-forming agent and first binder are dry-mixed for 1 to 2 hours to obtain a mixed material; deionized water accounting for 40 to 60% of the mass of the mixed material is added thereto, and the mixture is stirred and refined at a constant temperature of 90 to 100°C for 1 to 2 hours to obtain a mud material; after the mud material is aged at room temperature for 12 to 24 hours, 2.45 to 2.55 g of the mud material is weighed and put into a mold, and extruded at a pressure of 10 to 12 MPa; the green body is sintered at 1250 to 1300°C, the heating rate is 5 to 10°C / min, and the insulation time is controlled to be 1 to 2.5 hours, to obtain a ceramic support body with an average pore size of 0.74 to 1.26 μm;
[0009] The mass percentages of the components in the mixture are: 89.3-96.3% of high-aluminum fly ash, 3.5-8.5% of pore former, and 0.2-2.2% of the first binder;
[0010] The moisture content of the mud is 16% to 18%;
[0011] The high-aluminum fly ash is high-aluminum fly ash that has passed through a 500-2500 mesh sieve, and the obtained particles have a particle size of 0.71 to 33.4 μm; the pore-forming agent is starch, and the binder is methyl cellulose;
[0012] (2) Preparation of coating solution
[0013] The kaolin, dispersant and deionized water are mixed in a ball mill at a speed of 500-700 r / min for 1-6 hours; then the second binder is added, and the mixture is further mixed in a ball mill at a speed of 100-200 r / min for 30-60 minutes to obtain a coating solution;
[0014] The coating solution contains 5-20wt% kaolin, 0.2-2wt% second binder, 0.3-2.7wt% dispersant, and the remaining components are water; the dispersant is polyethylene glycol, and the second binder is polyvinyl alcohol;
[0015] (3) Preparation of filtration layer
[0016] The coating liquid is sprayed on the surface of the support body by a spraying method, and then sintered after drying for 12 to 24 hours to obtain a high-aluminum fly ash-kaolin composite ceramic membrane with an average pore size of 127 to 401 nm;
[0017] The drying temperature is 25°C to 100°C; the sintering temperature is 950°C to 1100°C, the heat preservation time is 0 to 3h, and the heating rate is 2 to 8°C / min.
[0018] The spraying time is 20 to 80 seconds for every 314 to 490 square millimeters of the support surface, and the spraying flow rate is 0.6 to 1.5 mL / min.
[0019] The composition and mass fraction of the high-aluminum fly ash include:
[0020] Al2O3: 60% to 65%, SiO2: 20% to 25%, CaO: 3% to 5%, Fe2O3: 2% to 5%, TiO2: 2% to 5%.
[0021] The kaolin composition and mass fraction include:
[0022] Al2O3: 45% to 50%, SiO2: 50% to 55%, Fe2O3: 0.5% to 1%, TiO2: 1 to 2%.
[0023] Furthermore, the method for preparing a high-alumina fly ash-kaolin composite ceramic membrane comprises the following steps:
[0024] Industrial wastewater with a particle concentration of 3 to 5 g / L is filtered using a composite ceramic membrane at 0.1 to 0.2 MPa;
[0025] The particle size of the particles ranges from 44 to 500 nm.
[0026] The essential features of the present invention are:
[0027] (1) In the current technology (patent CN116375453B), increasing the sintering temperature can improve the compressive strength of the support, but it will significantly reduce its porosity and water flux. The present invention does not increase the sintering temperature but prolongs the holding time, thereby improving the porosity and water flux of the support while also meeting the compressive strength requirements.
[0028] (2) Kaolin is selected as the raw material, and its cheapness and hydrophilicity are utilized to produce a low-cost, high-performance composite ceramic membrane, which improves the filtration accuracy while reducing the cost of ceramic membrane preparation.
[0029] (3) The spraying method is used to prepare the filter, which effectively avoids the defect transmission on the support. At the same time, the filter layer micro-penetrates into the support, ensuring the combination of the filter layer and the support without blocking the holes.
[0030] Beneficial effects of the present invention:
[0031] (1) Industrial waste high-aluminum fly ash is used as raw material to prepare a ceramic support, whose porosity is 35-43%, average pore size is 0.74-1.26 μm, bending strength is 16-32 MPa, and water flux is 7941-14716 L / h·m 2 Compared with the flexural strength of the support body in patent CN116375453B of 7MPa-28MPa, the water flux is 1800-4100L / h·m 2 MPa, a significant improvement.
[0032] (2) The low-cost material kaolin is also used as the raw material for the filter layer to produce a high-alumina fly ash-kaolin composite ceramic membrane with a water flux of 1165-4080 L / h·m 2 ·bar, the average pore size is 127~401nm. The interception rate of industrial wastewater with an average particle size of 200nm reaches 99.2~99.6%. Compared with the average pore size of fly ash-alumina double-layer composite ceramic membrane in patent CN109126482B, which is 100~300nm, the water flux is 400~2500L / h·m 2 ·bar, the water flux of the present invention is high and the raw materials are cheap and the preparation cost is low.
[0033] (3) The spraying method is used to prepare the filter layer, which can effectively avoid the transmission of defects on the support. At the same time, the filter layer micro-penetrates into the support, ensuring the interface bonding strength between the filter layer and the support. After multiple forward and reverse flushing, the pore size change of the composite membrane is less than 5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a physical picture of the support body and the composite ceramic membrane;
[0035] Figure 2 The surface SEM images of the support body at different holding times described in Examples 1-4;
[0036] Figure 3 The XRD diagrams of the support body at different holding times described in Examples 1-4;
[0037] Figure 4The effect of the holding time on the flexural strength of the support body described in Examples 1-4;
[0038] Figure 5 Surface SEM images of the composite ceramic membranes at different sintering temperatures described in Examples 9 and 15-17;
[0039] Figure 6 The effect of spraying time on the water flux of the composite ceramic membrane described in Examples 9 and 18-20;
[0040] Figure 7 Schematic diagram of the water flux test device. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should be protected by the present invention.
[0042] The high-aluminum fly ash and kaolin involved in the present invention are well-known materials. The composition and mass fraction of the high-aluminum fly ash are as follows: Al2O3: 63.4%, SiO2: 24.8%, CaO: 3.68%, Fe2O3: 2.61%, TiO2: 2.53%; after passing through a 500-2500 mesh sieve, high-aluminum fly ash particles with a particle size concentrated in the range of 0.71 to 33.4 μm are obtained.
[0043] The composition and mass fraction of kaolin are as follows: Al2O3: 45.8%, SiO2: 50.7%, Fe2O3: 0.7%, TiO2: 1.31%, but not limited thereto.
[0044] Example 1
[0045] This embodiment provides a method for preparing a ceramic support body from high-alumina fly ash, the method comprising the following steps:
[0046] Add materials according to the mass ratio of fly ash 93.3%, pore-forming agent starch 6%, and binder methyl cellulose 0.7%, and dry stir the materials at room temperature for 2 hours. Add distilled water accounting for 50% of the mass of the mixed materials to the evenly mixed materials, stir at a constant temperature of 100°C for 1.5 hours to refine the mud, and finally control the water content (mass percentage) of the mud to be 17%. Weigh 2.5g of mud into a mold and extrude it at 10MPa. After aging the green body at room temperature for 12 hours, put it into a muffle furnace for sintering. The heat treatment process of the support body is: heat up from room temperature to 300°C at 10°C / min, keep warm for 1.5 hours; heat up from 300°C to 650°C at 10°C / min, keep warm for 1.5 hours; heat up from 650°C to 1300°C at 5°C / min, keep warm for 1.5 hours. The average pore size of the support was 918 nm, the porosity was 40.54%, the flexural strength was 24.9 MPa, and the water flux was 9561.3 L / h·m 2 ·bar.
[0047] Embodiment 2-8
[0048] The other steps are the same as those in Example 1, except for the differences shown in Table 1.
[0049] Table 1
[0050] Example No. Pore-forming agent addition amount (%) Binder addition amount (%) Insulation time (h) 2 6 0.7 1 3 6 0.7 2 4 6 0.7 2.5 5 8.5 0.7 1.5 6 3.5 0.7 1.5 7 3.5 1.2 1.5 8 3.5 2.2 1.5
[0051] from Figure 2 It can be seen that with the increase of holding time, the mullite in the support gradually grows from fuzzy clusters to slender needles.
[0052] from Figure 3 It can be seen that with the increase of the holding time, the diffraction peak intensity of the mullite in the support powder gradually increases.
[0053] from Figure 4 It can be seen that with the increase of the holding time, the compressive strength of the support body increases from 23 MPa to 32 MPa, which is consistent with the gradual growth of mullite and the increase in the intensity of the mullite diffraction peak mentioned above. Increasing the holding time can effectively improve the compressive strength of the support body.
[0054] Example 9
[0055] This embodiment provides a method for preparing a high-alumina fly ash-kaolin composite ceramic membrane, the method comprising the following steps:
[0056] Kaolin, dispersant polyethylene glycol and deionized water were ball milled at a speed of 600r / min for 3 hours, while maintaining their mass at 90g. Then, the binder polyvinyl alcohol was added to maintain the total mass of the coating solution at 180g, and the coating solution was obtained after further mixing at a speed of 200r / min in the ball mill for 30 minutes. The mass ratio of kaolin, dispersant and binder is 5%:2.5%:1.5%. The coating solution was sprayed on the surface of the support with a diameter of 22mm prepared in Example 1 by spraying, with a spraying flow rate of 0.9mL / min and a spraying time of 40s. The heat treatment process of the composite ceramic membrane is: drying the green body at a temperature of 40°C for 12h. Heating from room temperature to 1000°C at 2°C / min and keeping warm for 2h. The thickness of the obtained composite ceramic membrane is 7.39μm, the average pore size is 135nm, and the water flux is 1990.6L / h·m 2 ·bar.
[0057] The porosity of the support was tested according to the "Test Method for Apparent Porosity of Porous Ceramics (GB / T1966-1996)", and the flexural strength of the support was tested according to the "Test Method for Flexural Strength of Porous Ceramics (GB / T1965-1996)". The average pore size of the support and composite ceramic membrane was measured by the BSD-PB-1526 membrane pore size analyzer of Beijing Best Instrument Technology Co., Ltd., and the water flux was measured by a laboratory-made device, such as Figure 7 shown.
[0058] The high-alumina fly ash-kaolin composite ceramic membrane prepared in this example was used to filter industrial wastewater, and the transmembrane pressure difference was 0.1 MPa. By testing the turbidity of the raw liquid and the permeate, the composite ceramic membrane had a retention rate of 99.6% for industrial wastewater with an average particle size of 200 nm.
[0059] The turbidity of the solution was measured by a LH-NTU2M portable turbidity meter produced by Beijing Lianhua Yongxing Technology Development Co., Ltd.
[0060] Table 2 is a comparison of the performance of the composite ceramic membrane prepared in this example and the alumina ceramic membrane reported in the literature (where the average pore size is in nm and the water flux is in L / h·m 2 ·bar, sintering temperature is ℃). It can be seen that the self-made composite ceramic membrane effectively reduces the cost while maintaining excellent performance.
[0061] Table 2
[0062] membrane Average pore size Water flux Sintering temperature Refs. <![CDATA[Al2O3]]> 75-93 1450-1730 1300 Ma(J.Water Process.Eng,2024,58:104739) <![CDATA[Al2O3]]> 100 460 - Yang(Sep.Purif.Technol.2022,300:121862) <![CDATA[Al2O3]]> 120 850 1350 Qin(Ceram Int,2020,46(9):13189-13197) <![CDATA[Al2O3]]> 260 1468±81 1300 Qin (RSC Advances, 2020, 10) <![CDATA[Al2O3]]> 130 550 1200 Song(RSC Advances,2017,43(13):10502-10507) Kaolin 135 1990.6 1000 Example 9
[0063] Examples 10-25
[0064] The other steps are the same as those in Example 9, except for the differences shown in Tables 3 and 4.
[0065] Table 3
[0066] Example No. Kaolin addition amount (%) Binder addition amount (%) Dispersant addition amount (%) 10 10 1.5 2.5 11 20 1.5 2.5 12 5 0.2 0.3 13 5 1 1 14 5 2 2.7
[0067] Table 4
[0068] Example No. Spraying time(s) Sintering temperature(℃) Insulation time (h) Heating rate (℃ / min) 15 40 950 2 2 16 40 1050 2 2 17 40 1100 2 2 18 20 1000 2 2 19 60 1000 2 2 20 80 1000 2 2 21 40 1000 0 2 22 40 1000 1 2 23 40 1000 3 2 24 40 1000 2 4 25 40 1000 2 8
[0069] from Figure 5 It can be seen that as the sintering temperature increases, the interaction between kaolin particles increases, and the particles migrate and combine to form a sintering neck. When the temperature is further increased, as the sintering neck grows, the membrane surface becomes more dense and the membrane pores gradually become larger.
[0070] from Figure 6 It can be seen that the membrane water flux gradually decreases with the increase of spraying time, from 4080L / h·m 2 bar drops to 1165L / h·m 2 ·bar.
[0071] The above are only a few specific embodiments of the present invention. The present invention is not limited to the above embodiments. Any modification, replacement, improvement, etc. made by ordinary technicians in this field without departing from the scope of the present invention should be within the protection scope of the present invention.
[0072] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a high-alumina fly ash-kaolin composite ceramic membrane, characterized in that: The method comprises the following steps: (1) Preparation of support The high-alumina fly ash, pore-forming agent and first binder are dry-mixed for 1 to 2 hours to obtain a mixed material; deionized water accounting for 40 to 60% of the mass of the mixed material is added thereto, and the mixture is stirred and refined at a constant temperature of 90 to 100°C for 1 to 2 hours to obtain a mud material; after the mud material is aged at room temperature for 12 to 24 hours, 2.45 to 2.55 g of the mud material is weighed and put into a mold, and extruded at a pressure of 10 to 12 MPa; the green body is sintered at 1250 to 1300°C, the heating rate is 5 to 10°C / min, and the insulation time is controlled to be 1 to 2.5 hours, and finally a ceramic support body with an average pore size of 0.74 to 1.26 μm is obtained; The mass percentages of the components in the mixture are: 89.3-96.3% of high-aluminum fly ash, 3.5-8.5% of pore former, and 0.2-2.2% of the first binder; The water content of the mud is 16% to 18%; the pore-forming agent is starch, and the first binder is methyl cellulose; (2) Preparation of coating solution The kaolin, dispersant and deionized water are mixed in a ball mill at a speed of 500-700 r / min for 1-6 hours; then the second binder is added, and the mixture is further mixed in a ball mill at a speed of 100-200 r / min for 30-60 minutes to obtain a coating solution; The coating solution contains 5-20wt% kaolin, 0.2-2wt% second binder, 0.3-2.7wt% dispersant, and the remaining components are water; the dispersant is polyethylene glycol, and the second binder is polyvinyl alcohol; (3) Preparation of filtration layer The coating liquid is sprayed on the surface of the support body by a spraying method, and then sintered after drying for 12 to 24 hours to obtain a high-aluminum fly ash-kaolin composite ceramic membrane with an average pore size of 127 to 401 nm; The drying temperature is 25°C to 100°C; the sintering temperature is 950°C to 1100°C, the heat preservation time is 0 to 3h, and the heating rate is 2 to 8°C / min.
2. The method for preparing the high-alumina fly ash-kaolin composite ceramic membrane according to claim 1, characterized in that: The high-aluminum fly ash is high-aluminum fly ash that passes through a 500-2500 mesh sieve, and the obtained particles have a particle size concentrated in the range of 0.71 to 33.4 μm.
3. The method for preparing the high-alumina fly ash-kaolin composite ceramic membrane according to claim 1, characterized in that: The spraying time is 20 to 80 seconds for every 314 to 490 square millimeters of the support surface, and the spraying flow rate is 0.6 to 1.5 mL / min.
4. The method for preparing the high-alumina fly ash-kaolin composite ceramic membrane according to claim 1, characterized in that: The composition and mass fraction of the high-aluminum fly ash include: Al2O3: 60% to 65%, SiO2: 20% to 25%, CaO: 3% to 5%, Fe2O3: 2% to 5%, TiO2: 2% to 5%.
5. The method for preparing the high-alumina fly ash-kaolin composite ceramic membrane according to claim 1, characterized in that: The kaolin composition and mass fraction include: Al2O3: 45% to 50%, SiO2: 50% to 55%, Fe2O3: 0.5% to 1%, TiO2: 1 to 2%.
6. Application of the method according to claim 1 in preparing high-alumina fly ash-kaolin composite ceramic membrane, characterized in that: The following steps are involved: Industrial wastewater with a particle concentration of 3 to 5 g / L is filtered using a composite ceramic membrane at 0.1 to 0.2 MPa; The particle size of the particles ranges from 44 to 500 nm.
Citation Information
Patent Citations
Preparation method of disc aluminum oxide filter membrane
CN107602091A
Ceramic flat plate film for water treatment and preparation method of ceramic flat plate film
CN108201715A
Liquid-sintered multichannel silicon carbide ceramic membrane element and preparation method thereof
CN108329033A
Liquid-phase sintered multi-channel silicon carbide ceramic membrane support and preparation method thereof
CN108395252A
Microfiltration ceramic membrane and preparation method thereof
CN108585883A